On Weakly $(τ_1,τ_2)$-continuous Functions (European Journal of Pure and Applied Mathematics, 2024)
Our main purpose is to introduce the concept of weakly (τ1, τ2)-continuous functions. Moreover, several characterizations of weakly (τ1, τ2)-continuous functions are considered.
Keywords: $τ_1τ_2$-open set; weakly $(τ_1,τ_2)$-continuous function